Association between dynapenia and decline in higher‐level functional capacity in older men with diabetes. Issue 9 (10th August 2018) - Ida, Satoshi; Murata, Kazuya; Nakadachi, Daiki; Ishihara, Yuki; Imataka, Kanako; Uchida, Akihiro; Monguchi, Kou; Kaneko, Ryutaro; Fujiwara, Ryoko; Takahashi, Hiroka
Abstract : Aim: The present study aimed to investigate an association between dynapenia or sarcopenia and higher‐level functional capacity in older diabetes patients. Methods: Diabetes outpatients aged ≥65 years were prospectively enrolled. Dynapenia and sarcopenia were defined by criteria of the Asian Working Group for Sarcopenia, and higher‐level functional capacity was assessed using the Tokyo Metropolitan Institute of Gerontology Index of Competence (TMIG‐IC). Multiple regression analysis included TMIG‐IC scores as the dependent variable and dynapenia or sarcopenia as the explanatory variables. Results: The present study included 204 patients. The regression coefficient of the relationship between dynapenia and covariance‐adjusted TMIG‐IC in men was −1.26 (95% confidence interval −2.35 to −0.17, P = 0.024), and that of sarcopenia and TMIG‐CI adjusted for covariates was 0.65 (95% confidence interval −1.26 to 2.58, P = 0.500). We observed no significant correlation between TMIG‐IC scores and dynapenia or sarcopenia in women. Conclusions: A statistically significant association was found between dynapenia and decline of higher‐level functional capacity in older men with diabetes.Geriatr Gerontol Int 2018; 18: 1393–1397 .